Diversidade evolutiva de morcegos: padrões geográficos e aplicações em conservação - Peixoto, Franciele Parreira (2013)
Aim: To investigate global patterns of phylobetadiversity (PBD) in bats, with the purpose to better understand the mechanisms underlying current biodiversity patterns. We also aimed to use a metric that allows partitioning PBD into two components to distinguish the relative roles of local (e.g. lineage filtering) and regional processes (e.g. speciation) in shaping broad-scale patterns of PBD. Furthermore, we analyzed the distance-decay relationship of phylogenetic beta diversity to provide more information about factors that act in the PBD patterns. Location: global, delimited by biogeographic regions. Methods: Using the global distribution of bats and a supertree available for most species, we calculated PBD using the complement of phylosor index. We used a null model to test if two assemblages were more or less phylogenetically dissimilar than expected by chance. In addition, we decoupled PBD into turnover and nestednessresultant components, providing information about two factors that produce differences in assemblage phylogenetic composition. We also performed a Mantel analysis to analyze the distance-decay patterns of PBD and its two components. Results: The most striking difference in PBD was found between the Old and New World “phylogenetic composition”. We found the lowest values of PBD between adjacent regions (i.e., Neotropical/Neartic; Indo-Malay/Paleartic), revealing a strong geographical structure in PBD. These values were even lower when the turnover component was analyzed, demonstrating the differences in the role of regional processes in shaping regional diversity. On the other hand, we found out that for some adjacent regions (e.g., Afrotropical/Paleartic), the observed PBD was higher than expected by chance and comparatively different from expected by the distance decay relationship. This value remained high, even when we analyzed just the PBD turnover component. This demonstrates that although these regions are relatively close in space, there are other factors driving phylogenetic differences between them (e.g. an environmental barrier). Main conclusions: Our analyses revealed differences in the expected patterns of bat PBD among regions, suggesting that at broad scales, besides the effects of distance and geographic barriers, we also have to consider the importance of environmental gradients when studying the phylogenetic origin of bat assemblages.